Deformation induced intermediate metastable lattice structures facilitate ordered B2 nucleation in a fcc-based high entropy alloy. Issue 1 (2nd January 2019) - Choudhuri, Deep; Shukla, Shivakant; Gwalani, Bharat; Banerjee, Rajarshi; Mishra, Rajiv S.
ABSTRACT: Ordered B2 precipitates typically nucleate at the grains-boundaries of fcc -based high entropy alloys. Here, we report a novel mixed-mode coupled displacive-diffusional transformation resulting in homogeneously distributed intra-granular B2 precipitates within the fcc matrix. Severe plastic deformation forms compositionally invariant, metastable distorted fcc structures, resembling hexagon-like templates, at the deformation twin-boundaries. These shear-induced hexagon-like templates correspond to the symmetry of the {111} bcc planes, and act as sites for B2 nucleation, establishing the fcc-bcc Kurdjumov–Sachs (KS) orientation relationship. However, the composition of these B2 precipitates is far-from-equilibrium. Subsequent isothermal annealing causes solute partitioning driving the composition of the B2 precipitates towards equilibrium. GRAPHICAL ABSTRACT: IMPACT STATEMENT: For the first time, a mixed mode displacive-diffusional fcc -to- bcc -ordered B2 transformation mechanism was revealed in a deformed fcc -based Al0.3 CoCrFeNi complex concentrated or high entropy alloy.